Longitudinal association of the anti-inflammatory serum marker GDF-15 with serum IgA and IgG in apparently healthy children - Gemma Carreras-Badosa (Nature Portfolio, 2021)
Abstract Both the innate and adaptive immune responses are deregulated in individuals with obesity and are key drivers of its associated metabolic alterations. Although the anti-inflammatory growth differentiation factor 15 (GDF-15) is a candidate protein against obesity, its mechanisms regulating the immune responses are not fully cleared. We examined whether GDF-15 was related to serum immunoglobulins in a children’s cohort assessed longitudinally during childhood. Results showed that circulating GDF-15 positively associated with IgA (p < 0.002) and IgG (p < 0.001) levels and the IgA*IgG product (p < 0.001) in apparently healthy children at both baseline (age 9) and follow-up (age 13). The associations were readily observed in heavier children (those with BMI-SDS above the median) as well as in children with higher renal fat accumulation (those with renal fat-to-height ratio above the median) and remained significant after correcting for possible confounding variables. Serum GDF-15 levels accounted for up to 16% of the variance of follow-up IgG levels and up to 14% of the variance of follow-up IgA*IgG product. The longitudinal associations of the anti-inflammatory GDF-15 with IgA, IgG and the IgA*IgG product in children with higher BMI or higher renal fat accumulation suggest a role of GDF-15 in human obesity through the regulation of the immune adaptive system.